The effect of earnings persistence on company performance in manufacturing companies listed on the Indonesia Stock Exchange 2004-2010 - Numala Ahmar (The Indonesian Accounting Review, 2014)
Good earnings quality reflects a good condition of the company, in which the persistence of earnings is sustainable profits, or for a long period. This study aims to empirically examine the effect of earning persistence on the performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The variable used is earnings persistence as an independent variable, and the dependent variable is the company performance measured by Tobin’s Q as a measure of company’s market performance and ROA as a measure of company’s operational performance. The research also uses control variable: Growth and Size. The samples are manufacturing companies listed on IDX for seven years in 2004-2010. Statistical test used is quantitative research by using One Way ANOVA (The Analysis of Variance), and cross tab to descriptive analysis. The main statistical test in this research is using multiple linearregressions. The result of this study shows that there is an effect of earning persistence on the company performance as measured by using both ROA and Tobin’s Q. It also shows that there is a significant effect of earnings persistence on the company performance as measured by using ROA and Tobin’s Q. Yet, controlled variable with regression equation of earning persistence toward ROA and Tobin’s Q, Growth and Size significantly have no effect on the company performance.